Nanostructured polyurethane-poly-lactic- co-glycolic acid scaffolds increase bladder tissue regeneration: an in vivo study - Yao C (Dove Medical Press, 2013)
Chang Yao,1 Matt Hedrick,1 Gyan Pareek,2 Joseph Renzulli,2 George Haleblian,2 Thomas J Webster3 1Nanovis LLC, West Lafayette, IN, 2Section of Minimally Invasive Urology, Alpert Medical School, Brown University, Providence, RI, 3Department of Chemical Engineering and Program in Bioengineering, Northeastern University, Boston, MA, USA Abstract: Although showing much promise for numerous tissue engineering applications, polyurethane and poly-lactic-co-glycolic acid (PLGA) have suffered from a lack of cytocompatibility, sometimes leading to poor tissue integration. Nanotechnology (or the use of materials with surface features or constituent dimensions less than 100 nm in at least one direction) has started to transform currently implanted materials (such as polyurethane and PLGA) to promote tissue regeneration. This is because nanostructured surface features can be used to change medical device surface energy to alter initial protein adsorption events important for promoting tissue-forming cell functions. Thus, due to their altered surface energetics, the objective of the present in vivo study was to create nanoscale surface features on a new polyurethane and PLGA composite scaffold (by soaking the polyurethane side and PLGA side in HNO3 and NaOH, respectively) and determine bladder tissue regeneration using a minipig model. The novel nanostructured scaffolds were further functionalized with IKVAV and YIGSR peptides to improve cellular responses. Results provided the first evidence of increased in vivo bladder tissue regeneration when using a composite of nanostructured polyurethane and PLGA compared with control ileal segments. Due to additional surgery, extended potentially problematic healing times, metabolic complications, donor site morbidity, and sometimes limited availability, ileal segment repair of a bladder defect is not optimal and, thus, a synthetic analog is highly desirable. In summary, this study indicates significant promise for the use of nanostructured polyurethane and PLGA composites to increase bladder tissue repair for a wide range of regenerative medicine applications, such as regenerating bladder tissue after removal of cancerous tissue, disease, or other trauma. Keywords: polyurethane, poly-lactic-co-glycolic acid, nanotechnology, nanostructured features, in vivo